Analysis of Asset Utilization in Public Services at Antapani District - Sahrul Haryadi (Social Impact Journal, 2022)
This research was conducted to analyze and explain the use of assets in public services at the Antapani District Office, Bandung City. This study uses a qualitative method with a descriptive approach. Then to obtain the data, researchers used techniques of observation, interviews, documentation, and literature study to strengthen and complement the primary data. Basically assets are objects that are held and owned to help an activity or work, both profit and non-profit, including in public service activities in Antapani District. This study shows that public services at the Antapani District office have been carried out properly by officers by utilizing the potential of existing assets, both fixed assets and other assets. However, in public service activities, asset performance has not been optimal because it is influenced by various factors. Especially in the fixed asset sector where some of the fixed assets in the Antapani District office require renovation or renewal in order to be able to increase the quantity and quality of public services at the Antapani District office. thus, requires a sizeable budget.